Avaliação do potencial antiofídico do extrato aquoso de Bellucia dichotoma Cogn. (Melastomataceae) elaborados de acordo com o uso tradicional - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Bothrops atrox is responsible for the majority of snakebites in northern Brazil and its poisoning is characterized by intense local and hemostatic disorders injuries. In some regions of the country where the care of accident victims by snakes is precarious, medicinal plants have been presented as an alternative treatment or as a complement in the absence of resources soroterápicos. The main goal of this study was to evaluate the anti-snakebite potential of aqueous extract of the bark of Bellucia dichotoma Cogn. (Melastomataceae) prepared in accordance with the traditional method. Initially, we investigated the potential of the extract (AEBd) to inhibit the major local (hemorrhagic, phospholipase A2 and edemainducing) activities of Bothrops atrox venom (BaV) and compared the pre-incubation method with the traditional method used in folk medicine. The concentrations of the phenolic components (tannins and flavonoids) in the extract were determined by colorimetric assays. To assess the action of AEBd on BaV, SDS-PAGE electrophoresis, zymography and Western-blot were carried out. As geographic distribution, soil type and climate can directly influence the biological potential of a species, we compared the potential of B. dichotoma collected in two different locations (Manaus, AM, and Santarém, PA) to inhibit the edemainducing, phospholipase A2, defibrinating and coagulant activities of BaV. We also investigated the antioxidant potential and cytotoxicity of the extracts using human fibroblasts (MRC-5 cell line). In an attempt to correlate the anti-snakebite potential of B. dichotoma with its chemical components, a preliminary HPLC-DAD method was developed to isolate the major components of the extract. The efficacy of the isolated components in inhibiting the hemorrhagic and phospholipase A2 activities of the venom was evaluated initially using a preincubation protocol and a venom:component ratio of 1:1 (w/w). Our results show that AEBd has a higher concentration of (condensed and hydrolysable) tannins than of flavonoids. The complete inhibition observed in this study when pre-incubation was used may be due to the presence of tannins in the extract. However, when AEBd was administered orally according to the traditional method, it was effective in inhibiting edema induced by BaV and enhanced the ability of the antivenom to inhibit edema formation. While the content of total phenolics, total tannins and hydrolysable tannins was greater in B. dichotoma extract collected in Manaus, this difference was not reflected in the anti-snakebite potential of the extracts collected in the two locations. Our results indicate that the two extracts have a high antioxidant potential and are not toxic in MRC-5 cells. It is noteworthy that a component in the FBd1 fraction of the aqueous extract blocked 100% of the hemorrhagic activity of BaV when pre-incubated with the venom. Studies to elucidate the chemical structure of this component are currently being carried out by our group.
Keywords: Plantas antiofídicas; Soro antibotrópico; Citotoxicidade; Perfil fitoquímico; Extratos vegetais; Ensaios colorimétricos; CIÊNCIAS BIOLÓGICAS